Taxonomy of Rufocumbre gen. nov., a new Moncini skipper genus (Lepidoptera: Hesperiidae: Hesperiinae) - Dolibaina, Diego Rodrigo; Mielke, Olaf Hermann Hendrik; Casagrande, Mirna Martins (Zootaxa, 2017)
Rufocumbre gen. nov. (type species: Rufocumbre celioi sp. nov.), a new genus of Neotropical skippers belonging to the tribe Moncini is described to include five species known only from Brazil. Four new species are described: Rufocumbre celioi sp. nov. from the states of Minas Gerais, Rio de Janeiro, São Paulo, Paraná, Santa Catarina and Rio Grande do Sul; Rufocumbre emeryi sp. nov. from the states of Mato Grosso, Distrito Federal, Goiás and Minas Gerais; Rufocumbre schneideri sp. nov. from the states of Tocantins, Distrito Federal, Minas Gerais and Paraná; and Rufocumbre lucasi sp. nov. from the states of Bahia and Minas Gerais. The taxon Cumbre belli eberti Evans, 1955 is transferred to the new genus and elevated to the species level, Rufocumbre eberti (comb. nov., stat. nov.). Adults, male androconia and genitalia of both sexes are illustrated for all species.